Adult attachment style and caregiver attitudes after raising a virtual child. (December 2016) - Symons, Douglas K.; Adams, Stephanie; Smith, Kathleen H.
Avoidance in adults is related to many negative aspects of caregiving and parenting. This was examined in a simulated parenting experience of 145 students who raised a virtual child from birth to age 19 using the website MyVirtualChild © . Avoidance and anxiety within adult relationships were assessed using the Experiences in Close Relationships–Relationship Structures questionnaire before and after this experience, and caregiver attitudes of positive feelings, perceptions of the child's security, and willingness to serve as an attachment figure were assessed after the experience. As predicted, avoidance and anxiety were negatively related to caregiver attitudes, with avoidance accounting for these relations. These results support the negative impact of avoidance on caregiver attitudes, even when the child is raised in Cyberspace.